Keterampilan Menulis Teks Lawakan Tunggal Menggunakan Aplikasi Tiktok Siswa Kelas X SMK Negeri 1 Kota Bengkulu - Amanda, Leony Chika; Trianto, Agus; Arono, Arono (UNIB Press, 2025)
Learning media is increasingly varied along with the development of technology, because many applications are specifically designed as learning media. This study aims to describe the skills of writing single joke texts using the TikTok application of class X students of SMK Negeri 1 Bengkulu City. This study uses a qualitative descriptive method. Data collection techniques in this study used observation, interview and documentation techniques. Data analysis was carried out by data reduction, data presentation, and drawing conclusions. The results of the writing skills study were carried out in the form of a single joke text writing test with aspects of the suitability of the contents of the single joke text, the accuracy of the structure of the single joke text, the accuracy of words, the suitability of capital letters and spelling, criticism and humor in the good category with a range of values ​​between 75-85. The average score of students from the results of the single joke text writing test is 81.07. Using the TikTok application in learning single jokes is the right choice as an effective learning medium because the TikTok application meets the learning needs of students who are interesting because of its novelty and has many features that can be implemented into learning.